IMPLEMENTASI TEKNOLOGI PEMBANGKIT LISTRIK TENAGA SURYA PADA SISTEM HIDROPONIK DAN AKUAPONIK DI SDI AS SALAM DAN SMPIT AS SALAM SERTA INTEGRASINYA DENGAN PROGRAM KKN - Baharuddin, Muhammad Fadly Zon; 'Atieq, Madza Awwalul; Prihartono, Mohammad Haikal Rizki; Chairunnisa, Fatma; Hamzah, Ilham Fathurrahman; Erenka, Salsabila Naja; Pangestu, Luhita Labibah; Yahya, Muhammad Izzuddin; Gibran, R M Avril (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2024)
Doctoral program of service at SDI As Salam and SMPIT As Salam aims to address issues in implementing urban farming by applying solar power technology to hydroponic and aquaponic systems. The methods used in this program include a participatory approach through brainstorming sessions and focus group discussions (FGD), technical training, and intensive mentoring. The results show that the installation of solar power systems successfully reduced electricity costs by up to 40% within the first three months. Additionally, the technical training provided has improved the technical knowledge and skills of 90% of the training participants. The program also increased environmental awareness and participation among students and staff. Challenges such as high initial costs and the need for routine maintenance present opportunities for future improvement through additional funding and ongoing training. The success of this program provides tangible benefits to the school and surrounding community and has the potential to be implemented in other schools.